Stability Indicating RP-HPLC Method for Selegiline Hydrochloride in Pharmaceutical Formulation - Nagras, M. A.; Kalaskar, Rahul C. (Asian Journal of Pharmaceutical Research and Development, 2014)
Stability indicating RP-HPLC method has been developed for the determination of Selegiline hydrochloride in pharmaceutical formulation. Chromatographic separation of Selegiline hydrochloride and its known impurities was achieved by using BDS Hypersil C18 (250 x 4.6 mm, 5 µm) column at temperature of 40˚C. Mobile phase composed ofAcetonitrile:Potassium di-hydrogen phosphate buffer adjusted at pH 4.0+0.5 (30:70v/v). Flow rate was 1.00 ml per min and the absorbance was measured at 205nm. The retention time of Selegiline hydrochloride was 5.7min, at runtime 10min. System suitability parameters like, tailing factor 1.1 and theoretical plates 6010 were calculated. The linearity of the method was evaluated from 25µg per ml to 100µg per ml for Selegiline hydrochloride by injecting 50µl of standard solution giving correlation coefficient 0.999. The developed method can be used or applied for the quantification of Selegiline hydrochloride in pharmaceutical products.